Tourism in Nepal: Opportunities, Challenges, and the Path to Sustainable Growth - Bhatt, Jagdish Chandra (Brixton Scholarly Review, 2025)
Nepal, a nation of breathtaking natural beauty, diverse cultures, and warm hospitality, holds immense potential as a global tourism destination. Over the years, my deep involvement in the hotel, travel, tourism, and education sectors, coupled with experiences from traveling to countries like India, Singapore, Thailand, Japan, Australia, and Dubai, has provided me with unique perspectives on the growth and challenges of Nepal's tourism industry. This article delves into the opportunities Nepal offers, focusing particularly on the Far-Western region, the obstacles the industry faces, and strategies to ensure sustainable tourism development. Drawing from my personal experiences and global exposure, this article aims to provide actionable insights for stakeholders in the tourism industry while contributing to the academic discourse.